Bricolage in labor organizing practices: Spanish and Italian migrant activists in Berlin - Castellani, S.; Roca, B. (Journal of Industrial Relations, 2022)
This article analyzes how Southern European workers create bricolage by combining creatively organized practices of collective action, such as those of conventional labor unions, with self-created practices when facing oppressive labor relations and widespread downgrading of social mobility. We compare two cases of networks formed by Spanish and Italian migrant workers in Berlin: the Grupo de Acción Sindical and Berlin Migrant Strikers. Drawing on an ethnographic study of these groups, the article argues that the networks have different logics of action and political strategies. Their dissimilarities are manifested in different outcomes and organizational dimensions. Key factors include their founding members' social and activist backgrounds and leaders' countries of origin. It can be argued that, through these networks, migrants produce and reproduce political practices and collective actions, shaping a transnational social space that connects migrants and non-migrant individuals and organizations from both origin and destination countries.